Penekanan Penyakit Lincat Tembakau Temanggung dengan Streptomyces spp. - Triwidodo Arwiyanto; Kharis Haryono; Achmadi Priyatmojo; Toekidjo Martoredjo; Gembong Dalmadiyo (Jurnal Perlindungan Tanaman Indonesia, 2007)
Streptomyces is one of a soil microorganisms which is rarely used by Indonesian researcher for biological control of planth pathogent. Local isolates of Streptomyces spp. were used in this study to control "lincat disease" of Temanggung tobacco. Ninety four isolates of Streptomyces were tested directly in the field to suppress the development of lincat disease in the field. Six isolates, i.e. Stre-4, Stre-7,Stre-48, Stre-61, Stre-66 and Stre-67 suppressed the disease development with various degree. It was likely that decreasing the concentration of bacterial antagonist gave better protection against the disease. In vitro experiments indicated that there was no correlation between inhibition pathogen in vitro and ability to suppress disease in the field. The result showed that selection of antagonist in vitro based on antibiosis will eliminate the chance to get other potential antagonist.